Article Withdrawal by ASERS Publishing - Fraudulent double submission and legal limitations - Integration Processes in the Agro-Industrial Complex of the Regions: Development and Environmental Problems - GLOTKO, Andrey; SYCHEVA, Irina; DUNETS, Alexander; POLTARYKHIN, Andrey; ZHURAVLEV, Pavel; TUBALETS, Anna (Journal of Environmental Management and Tourism; Vol 10 No 3 (2019): JEMT Volume X Issue 3(35) Summer 2019, 2019)
This paper is devoted to the methodology for assessing the development of extra- and intra-integration structures. This methodology consists of three levels of economic assessment of the agro-industrial sector: the regional level, the economic sector level, and the enterprise level. The agro-industrial complex of the Altai Republic has positive business dynamics due to the development of the livestock industry. Through assessing the business outlook for agro-industrial integration using the three levels, it has been determined that the livestock industry has the greatest potential for creating large integrated structures in the Altai Republic. The study justifies the need for creating an internal cluster (intra-cluster) in the maral deer breeding sphere of the Altai Republic, and an external cluster (extra-cluster) in the sphere of meat-and-dairy cattle breeding in the Altai Republic and the Altai Territory. The authors propose a ‘business-as-usual’ and a target scenario for the development of the agro-industrial complex of the Altai Republic until 2025. The target scenario reflects the effectiveness of the proposed measures for the development of the agro-industrial complex of the Altai Republic. According to this scenario, the formation of intra-clusters and extra-clusters in 2025 will lead to an increase in total profits of the livestock industry enterprises under analysis by 451 million rubles and of budget allocations by 194.3 million rubles. The goal of this study is to develop theoretical and methodological guidelines for shaping and developing integrated structures in the agro-industrial complex.